2004
DOI: 10.1021/ma035527l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Coil Block on the Properties of Rod−Coil Diblock Copolymers with Oligofluorene as the Rigid Segment

Abstract: Rod−coil diblock copolymers of 2-hydroxyethyl methacrylate (HEMA) with well-defined oligofluorene initiator were synthesized using the atom transfer radical polymerization (ATRP) technique. The resulting copolymers were characterized using spectroscopic (1H NMR, GPC), optical (UV, photoluminesence), and thermal (DSC) techniques. The incorporation of the initiator into the polymeric chain was confirmed by spectroscopic methods, while strong evidence for microphase separation was obtained both from DSC and AFM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 85 publications
(37 reference statements)
0
53
0
Order By: Relevance
“…The polymers can be applied in LEDs displaying stable blue light emission, Figure 25. 192 Stupp et al reported the synthesis and characterization of triblock rod-coil molecules 74-78 consisting of diblock coil segments of polystyrene and polyisoprene and oligo(p-phenylenevinylene)s (OPVs) as rod segments. On the basis of TEM and X-ray diffraction data, 75-78 formed self-organized nanostructures ( Figure 26) whereas 74 lacked any order, showing that π aggregation of OPV units is not the dominant factor in the self-assembly process.…”
Section: Monodisperse Main-chain π-Conjugated Blocksmentioning
confidence: 99%
“…The polymers can be applied in LEDs displaying stable blue light emission, Figure 25. 192 Stupp et al reported the synthesis and characterization of triblock rod-coil molecules 74-78 consisting of diblock coil segments of polystyrene and polyisoprene and oligo(p-phenylenevinylene)s (OPVs) as rod segments. On the basis of TEM and X-ray diffraction data, 75-78 formed self-organized nanostructures ( Figure 26) whereas 74 lacked any order, showing that π aggregation of OPV units is not the dominant factor in the self-assembly process.…”
Section: Monodisperse Main-chain π-Conjugated Blocksmentioning
confidence: 99%
“…Rod-coil block copolymers consisting of conjugated segments connected with flexible segments have been the subject of extensive studies because of their unusual morphologies and photophysical behavior in both solution and solid state [171][172][173][174][175][176]. For this kind of block copolymers, a combination of complementary virtues from both rod and coil blocks can be envisioned.…”
Section: Polyfluorenes With Rod-coil Structurementioning
confidence: 99%
“…The increase in solvent polarity and evaporation rate causes an increase in nanoribbon dimensions. Oligo-or PF-based rod-coil diblock copolymers of PF-37-42 have been observed to form nanowires and nanofibres with widths of several 10 nm, and chain packing in the assembled entities has been studied by AFM, XRD and theoretical modelling [244,245,[259][260][261][262][263][264][265]. Rod-coil co-PFs of PF-42 enable morphological transformation through the variation of coil-segment fractions and the amount of immiscible solvent [246] Recently, nanowire thin films have been obtained via nanoscale phase separation of fully conjugated block copolymers such as PF-28, 29 [266].…”
Section: Introductionmentioning
confidence: 99%